Termitaria enhance soil and forest diversity in Deciduous Dipterocarp Forest, Northern Thailand - Kaewfoo, Manop; Bunyavejchewin, Sarayudh; Marod, Dokrak; Wiwatwittaya, Decha; Baillie, Ian C.; Davies, Stuart J.; Hallett, Stephen H. (Cambridge University Press, 2024)
We characterised the soils and vegetation in 15 sets of four quadrats on and around mounds of Macrotermes annandalei (Isoptera, Macrotermitinae) on a plain of deep dystric clay over limestone in Deciduous Dipterocarp Forest in Northern Thailand. Termites have excavated the mounds from the deep calcareous substrate. The mound soils have darker subsoils, larger contents of clays and exchangeable cations, and higher pH values than the surrounding dystric clay loams. The thickets on the mounds are visually different from the surrounding Deciduous Dipterocarp Forest. They have few dipterocarps and are floristically similar to the regionally important Mixed Deciduous Forest. The clear visual differences are confirmed by floristic similarity, cluster, and canonical correspondence analyses for each of the tree, sapling and seedling size classes. The differences between the mound clays and surrounding red clay loams and the associations between soil and forest types are confirmed by ‘t tests’ and the significant correlations of the soil base status with the main floristic axis of the canonical correspondence analyses. Soil variability due to termites and other agents of pedoturbation can significantly contribute to short-range floristic and structural diversity in some dry tropical forests.
Keywords: cationic nutrients; Deciduous Dipterocarp Forest; Mixed Deciduous forest; Pedoturbation; Termitaria